Pengaruh Sales Promotion Flash Sale dan Price Discount Terhadap Perilaku Impulse Buying Pada Marketplace Tokopedia - Hasbi, Imanuddin; Iftikhar, Farhan Dhiya (eProceedings of Management, 2024)
Tokopedia, as one of the largest marketplace platforms in Indonesia, offers various shopping conveniences forconsumers. This is proven by previous research which found that Tokopedia has a high level of ease of use comparedto other e-commerce platforms. The convenience offered encourages consumers to shop impulsively. Based on thephenomenon found on social media, it shows that consumers make impulse buying on Tokopedia because of the flashsale sales promotion program and also price discounts. This study aims to determine: (1) the effect of sales promotionflash sales on impulse buying behavior in the Tokopedia marketplace, (2) the effect of price discounts on impulsebuying behavior in the Tokopedia marketplace, (3) the effect of sales promotion flash sales and price discounts onimpulse buying behavior in the Tokopedia marketplace simultaneously. This research is quantitative research withmultiple linear regression analysis with support from SPSS Statistics 26 software. In this study using a survey methodwith a sample size of 150 Tokopedia user respondents. The results of this study: partially there is a positive andsignificant effect of the flash sale variable on the impulse buying variable, and partially there is a positive andsignificant effect of the price discount variable on the impulse buying variable. Simultaneously, it shows that the flashsale and price discount variables jointly affect the impulse buying variable (based on the results of the F test). Keywords-flash sale, price discount, impulse buying